Perspektif Keluarga tentang Praktik Manajemen Diri Diabetes Sebuah Studi Kualitatif - Sairomaito Harahap; Mula Tarigan; Siti Zahara Nasution; Muhammad Sukri Tanjung (Universitas Pahlawan Tuanku Tambusai, 2025)
Diabetes Mellitus (DM) is one of the global health problems that continues to increase in number from year to year. Diabetes self-management practice which is an important component in diabetes management, always involving the family in its implementation. This study aimed to explore family perspectives on diabetes delf-management practices. The research design used was a qualitative-descriptive phenomenology. Participants in this study were family members who cared for patients. A total participants of 10 people were recruited by purposive sampling at the Prof.dr. Chairuddin P Lubis Hospital Medan, North Sumatra, from March to Mei 2025. Data was collected through in-depth interviews with a semi-structured questions and analyzed using Colaizzi method. This study found 4 themes and 10 theme clusters related to diabetes self-management practices as follows: diet patterns (non-adherence to healthy diet, food preparation by the patient, and the patient sets his own dietary portions), physical exercise (not regularly doing physical exercise, independent physical exercise, reasons of not doing physical exercise), medications (non-adherence to medication and medication management by patients), and spirituality (patients routinely carry out religious activities and non-religious spiritual needs). According to the family's perspective, diabetic patients have not optimally implemented diabetes self-management practices in diet, medication, and exercise. Health workers are expected to provide support to patients and families so that diabetes self-management practices can run more optimally. Keywords: Type 2 diabetes, self-management practice, family, perspective, phenomenology